ANALISA RISIKO DAN KEUNTUNGAN INVESTASI SAHAM BATU BARA DI BURSA EFEK INDONESIA (Tahun 2010-2014) - Siti Nur Zahroh (Jurnal Ekonomi Pembangunan, 2015)
This research was motivated by the increasing value of the production and consumption of coal from year to year, but is not offset by an increase in new investment in this sector. Each selection of investment decisions certainly linked to the degree of risk and benefit ratio, in order to know how much future investment results that will be obtained with the level of risk to a minimum. The purpose of this study was to measure the level of risk and benefit ratio of shares in a coal mining company listed on the Stock Exchange during the study period 2010-2014. Calculation of the level of risk in this study was measured by VaR (Value at Risk) and the profit rate is measured with RAROC (Risk Adjusted Return on Capital). The results of this study indicate that the coal mining stocks are a potential value loss (high risk low return). The highest VaR value during the study period experienced by PKPK of 0.64300 or 64.30% in 2010. The market value of the highest RAROC during the observation period by ITMG in 2010 amounted to 0.4304 or 43%.